2010
DOI: 10.1080/10913671003715565
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Moderate to Vigorous Physical Activity in High School Physical Education: A Pedometer Steps/Minute Standard

Abstract: The primary objective of this research was to quantify the recommended minimum level (i.e., 50% of the class time) of moderate to vigorous physical activity within high school physical education via pedometry steps/min. A secondary objective was to explore the influence of lesson duration (i.e., traditional vs. block schedules) on quantifying moderate to vigorous physical activity via steps/min. Data (N = 218) were collected from 27 physical education classes taught by 10 certified physical educators in 6 scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 14 publications
2
25
2
2
Order By: Relevance
“…In this sense, Scruggs et al 21 used the same evaluation method in the physical education class and found similar results. In addition, studies that evaluated PA through other methods also showed that boys are more active in both physical education class 7,22,23 and school recess 14,24 .…”
Section: Discussionsupporting
confidence: 57%
“…In this sense, Scruggs et al 21 used the same evaluation method in the physical education class and found similar results. In addition, studies that evaluated PA through other methods also showed that boys are more active in both physical education class 7,22,23 and school recess 14,24 .…”
Section: Discussionsupporting
confidence: 57%
“…Scruggs found greater steps/min intervals for the 50% MVPA recommendation of 79-86 among participants of a similar age (12.9 -13.8 years in Scruggs 2007a& Scruggs 2013b. A higher steps/min interval of 80-88 steps/min was found in another study among older participants (16.5 years in Scruggs et al, 2010). It is unclear what may account for the difference in steps/min intervals identified between the present study and Scruggs' research.…”
Section: Pedometer Step Per Minute Guidelines Corresponding To Spendicontrasting
confidence: 43%
“…For the one third MVPA criteria, similar pedometer steps/min intervals were found across four studies ranging from 60.8-65.0, mainly among primary children aged between 6.9 and 13.8 years old (Scruggs et al, 2003, Scruggs, Beveridge, Watson, & Clocksin, 2005, Scruggs 2007b, Scruggs 2013b. For spending half of PE class time engaged in MVPA as recommended by The United States Department for Health and Human Services (2009), two studies found greater steps/min ranging from 79.1-88.0 for youth aged 12.5-15.5 years (Scruggs 2007a& Scruggs, Mungen & Oh, 2010. A follow up study sought to identify optimal steps/min intervals for both 33.33% and 50% MVPA criteria from combined data sets from previous research (Scruggs, 2013b).…”
Section: Pedometer Steps Per Minute Guidelines In Physical Education mentioning
confidence: 99%
See 2 more Smart Citations